The effects of packaging type on the quality characteristics of fresh raw pistachios (Pistacia vera L.) during the storage - Ozturk, Ismet; Sagdic, Osman; Yalcin, Hasan; Capar, Tugba Dursun; Asyali, Musa Hakan (ELSEVIER, 2016)
In this study, the effect of different packaging systems on physicochemical, microbiological, aroma, color and sensory characteristics of fresh raw pistachios during storage was evaluated. Fresh raw pistachios were stored at vacuum (VP), modified atmosphere (MAP) and conventional packaging (CP) at 4 degrees C for 30 days. Total mesophilic bacteria (TMAB) counts and free fatty acids (FFA) values were the most discriminating parameters. At the end of the storage, FFA level and TMAB population of the samples stored in the CP were the highest while VP and MAP enabled lower levels of FFA and TMAB, respectively. During the storage palmitic acid content increased whereas linoleic acid level decreased in the all types of packaging. No significant differences were found in other fatty acids during storage. Sensory analysis showed variable results among the three packaging systems. In conclusion, the use of MAP was generally recommended for the maintenance of quality of fresh raw pistachio for longer storage periods. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Nut; Modified atmosphere packaging; Aroma; Sensory; Fatty acid; PHYSICAL-PROPERTIES; VOLATILE COMPOUNDS; GAMMA-IRRADIATION; MOISTURE-CONTENT; NUTS; ATMOSPHERE; KERNEL; VARIETY; Food Science & Technology